The structural geometry, metamorphic and magmatic evolution of the Everest massif, High Himalaya of Nepal-South Tibet - Searle, M; Simpson, R; Law, R; Parrish, R; Waters, D (2003)
This paper presents a new geological map together with cross-sections and lateral sections of the Everest massif. We combine field relations, structural geology, petrology, thermobarometry and geochronology to interpret the tectonic evolution of the Everest Himalaya. Lithospheric convergence of India and Asia since collision at c. 50 Ma. resulted in horizontal shortening, crustal thickening and regional metamorphism in the Himalaya and beneath southern Tibet. High temperatures (>620 °C) during sillimanite grade metamorphism were maintained for 15 million years from 32 to 16.9 ± 0.5 Ma along the top of the Greater Himalayan slab. This implies that crustal thickening must also have been active during this time, which in turn suggests high topography during the Oligocene-early Miocene. Two low-angle normal faults cut the Everest massif at the top of the Greater Himalayan slab. The earlier, lower Lhotse detachment bounds the upper limit of massive leucogranite sills and sillimanite-cordierite gneisses, and has been locally folded. Ductile motion along the top of the Greater Himalayan slab was active from 18 to 16.9 Ma. The upper Qomolangma detachment is exposed in the summit pyramid of Everest and dips north at angles of less than 15°. Brittle faulting along the Qomolangma detachment, which cuts all leucogranites in the footwall, was post-16 Ma. Footwall sillimanite gneisses and leucogranites are exposed along the Kharta valley up to 57 km north of the Qomolangma detachment exposure near the summit of Everest. The amount of extrusion of footwall gneisses and leucogranites must have been around 200 km southwards, from an origin at shallow levels (12-18 km depth) beneath Tibet, supporting models of ductile extrusion of the Greater Himalayan slab. The Everest-Lhotse-Nuptse massif contains a massive ballooning sill of garnet + muscovite + tourmaline leucogranite up to 3000 m thick, which reaches 7800 m on the Kangshung face of Everest and on the south face of Nuptse, and is mainly responsible for the extreme altitude of both mountains. The middle crust beneath southern Tibet is inferred to be a weak, ductile-deforming zone of high heat and low friction separating a brittle deforming upper crust above from a strong (?granulite facies) lower crust with a rheologically strong upper mantle. Field evidence, thermobarometry and U-Pb geochronological data from the Everest Himalaya support the general shear extrusive flow of a mid-crustal channel from beneath the Tibetan plateau. The ending of high temperature metamorphism in the Himalaya and of ductile shearing along both the Main Central Thrust and the South Tibetan Detachment normal faults roughly coincides with initiation of strike-slip faulting and east-west extension in south Tibet (<18 Ma).